Influence of experimental hypoxia on the content of toxic and trace microelements in the tissues of newborn rats - Tarasova I. (Морфологія, 2011)
Organs of newborn rats (cerebrum, heart, liver, kidneys) are characterized by a high contains of microelements. Review of toxic and ultramikroelements in the tissues of vital organs in case of severity is essential for understanding hypoxic-ischemic lesions in neonatology. In this paper we used hypobaric model of hypoxia, the study conducted on 60 laboratory rats for the first and seventh day of life. By the seventh day of life the content of chrome and manganese decreases. In cerebrum contain of lead is the most. Hypoxia leads to a considerable decrease of the level of manganese. Severe hypoxia leads to the decrease of contain of chrome and cobalt. Hypoxia causes increase of accumulation of lead in heart and kidneys in 8 times, in liver – in 3 times, and also in cerebrum (28, 2%).